Assessing Middle School Students’ Understanding and Implementation of Social and Emotional Competencies: A Study Conducted in Private Schools in Mount Lebanon - Issa, John; Berberian, Pekiza (European Journal of Applied Sciences, 2024)
The changes taking place in this fast-paced world "have led to the rise of social and emotional processes" (Cefai et al., 2020, p.3). Although Social Emotional Learning (SEL) encompasses many aspects, the primary elements include self-awareness, social awareness, responsible decision making, self-management, and relationship management (Merrell & Gueldner, 2010, p.40). Acknowledging the importance of adolescence as the critical period to explore developments in understanding oneself and others, this study addresses three primary research questions. The first question examines the extent to which middle school students possess SEL competencies in Lebanese private middle schools. The second question explores whether middle school students from lower socioeconomic status differed in their SEL competencies from those coming from higher socioeconomic status (SES). The third question assesses the presence of gender differences in possessing socio-emotional competencies in middle school students. This study’s findings showed that middle school students (n = 165) in Lebanese private schools possess social and emotional competencies to varying extents. The results provide further evidence for the association of SES factors on an adolescents’ acquisition and development of social-emotional competencies, self-control specifically. The findings confirm that, in addition to socioeconomic status (SES), personal and environmental factors—such as community and culture—play a crucial role in shaping the social-emotional development of middle school students. The given recommendations affirm that different stakeholders, including educational policymakers, schools, teachers, and families in Lebanon, should be active partners in supporting SEL by providing various services in safe and nurturing environments.